Evaluation of recombinant baculovirus clearance during rAAV production in Sf9 cells using a newly developed fluorescent-TCID50 assay - Luo, Ningguang; Chen, Xiangqun; Li, Jinzhong; Huynh, Derrick; Li, Ying; Ou, Li; Liu, Shengjiang (Frontiers in Medicine, 2024)
Introduction Recombinant adeno-associated virus (rAAV) vectors provide a safe and efficient means for in vivo gene delivery, although its large-scale production remains challenging. Featuring high manufacturing speed, flexible product design, and inherent safety and scalability, the baculovirus/Sf9 cell system offers a practical solution to the production of rAAV vectors in large quantities and high purity. Nonetheless, removal and inactivation of recombinant baculoviruses during downstream purification of rAAV vectors remain critical prior to clinical application. Methods The present study utilized a newly developed fluorescent-TCID50 (F-TCID50) assay to determine the infectious titer of recombinant baculovirus (rBV) stock after baculovirus removal and inactivation, and to evaluate the impact of various reagents and solutions on rBV infectivity. Results and discussion The results showed that a combination of sodium lauryl sulfate (SLS) and Triton X-100 lysis, AAVx affinity chromatography, low pH hold (pH3.0), CsCl ultracentrifugation, and NFR filtration led to effective removal and/or inactivation of recombinant baculoviruses, and achieved a log reduction value (LRV) of more than 18.9 for the entire AAV purification process. In summary, this study establishes a standard protocol for downstream baculovirus removal and inactivation and a reliable F-TCID50 assay to detect rBV infectivity, which can be widely applied in AAV manufacturing using the baculovirus system.